The Rational Utilization of Catchment Areas in India - STRACEY, P.D. (Journal of Soil and Water Conservation, 2022)
The problem of the proper maintenance and utilization of the catchment areas of the many dams which are being con- structed in India today has got to be faced sooner or later. It may be accepted as undisputed that the planners have given this aspect of the problem very little consideration when the idea for a particular dam, whetner for flood control, irrigation or hydro-electric power (developrnent, has been mooted. The engineers have to build the project may have given the question a little more thought than the planners, but their point of view is possibly solnewhat restricted and confined to the actual technical aspect of their task. From time to time alarmning reports or forecaste   of the shortening effect on the life of an expensive dam through the filling up of its reservoir by sediment as the result of unrestricted erosion of the catchment area.